2010
DOI: 10.1111/j.1460-9568.2010.07230.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of mediolateral functional dichotomy in the rat nucleus accumbens during cocaine self‐administration II: phasic firing patterns

Abstract: In the cocaine self-administering rat, individual nucleus accumbens (NAcc) neurons exhibit phasic changes in firing rate within minutes and/or seconds of lever presses (i.e. slow phasic and rapid phasic changes, respectively). To determine whether neurons that demonstrate these changes during self-administration sessions are differentially distributed in the NAcc, rats were implanted with jugular catheters and microwire arrays in different NAcc subregions (Core, Dorsal Shell, Ventromedial Shell, Ventrolateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 51 publications
(127 reference statements)
5
44
0
1
Order By: Relevance
“…Previous analyses of NAcc slow phasic firing patterns in this laboratory (Peoples and West, 1996; Peoples et al 1998; Fabbricatore et al 2010) have defined two types of post-press changes (increase and decrease), both with three different kinds of reversal patterns (early, progressive, and late). A new slow phasic assessment procedure, which included the PCA based categorization, was developed for the present study.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous analyses of NAcc slow phasic firing patterns in this laboratory (Peoples and West, 1996; Peoples et al 1998; Fabbricatore et al 2010) have defined two types of post-press changes (increase and decrease), both with three different kinds of reversal patterns (early, progressive, and late). A new slow phasic assessment procedure, which included the PCA based categorization, was developed for the present study.…”
Section: Methodsmentioning
confidence: 98%
“…While the schedule of reinforcement used was a 40 second fixed interval, responses during cocaine self-administration are regulated by the intravenous dose (Pickens and Thompson, 1968). The dose used in the current study generates inter-response intervals between 6 and 8 min (Peoples and West, 1996; Peoples et al 1998; Fabbricatore et al 2010). Prior to recordings, all self-administration sessions were six hours in duration or 80 infusions were earned, whichever occurred first.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the extent to which these mesoaccumbens DA-glutamate fibers participate in the neurobiology of drugs of abuse remains to be determined, we speculate that these axons may participate in the regulation of neuronal activity in cocaine self-administration. Specifically, electrophysiological recordings have shown that nAcc neurons exhibit rapid phasic firing patterns to related cues and actions to obtain the drug (Peoples et al, 1998; Ghitza et al, 2003, 2004, 2006; Fabbricatore et al, 2009, 2010; Coffey and Barker et al, 2015). The nAcc neurons also exhibit slow-phasic and tonic changes in firing rate that correlate with the pharmacological effects of cocaine, and do not correlate with the rapid phasic firing patterns (Fabbricatore et al, 2010).…”
Section: Functional Diversity By Vta Neuronsmentioning
confidence: 99%
“…Specifically, electrophysiological recordings have shown that nAcc neurons exhibit rapid phasic firing patterns to related cues and actions to obtain the drug (Peoples et al, 1998; Ghitza et al, 2003, 2004, 2006; Fabbricatore et al, 2009, 2010; Coffey and Barker et al, 2015). The nAcc neurons also exhibit slow-phasic and tonic changes in firing rate that correlate with the pharmacological effects of cocaine, and do not correlate with the rapid phasic firing patterns (Fabbricatore et al, 2010). Furthermore, slow phasic pharmacologic and rapid phasic behavioral firing patterns are similarly processed in downstream accumbal targets (ventral pallidum and lateral preoptic area; Root et al, 2012, 2013; Barker et al, 2014).…”
Section: Functional Diversity By Vta Neuronsmentioning
confidence: 99%